1996
DOI: 10.1016/0014-5793(96)00404-8
|View full text |Cite
|
Sign up to set email alerts
|

Substrate specificity of monomeric and dimeric α‐sarcin

Abstract: The substrate specificity of monomeric and dimeric forms of c~-sarcin was investigated by membrane blotting procedures. Dimeric ~-sarcin fails to inactivate ribosomes as well as to hydrolyze mini-stem-loop RNA, whereas monomeric Separation ofdimer andmonomer ofoasarcin on PVDFmembraneMonomeric and dimeric a-sarcin were separated by electrophoresis oc-sarcin catalyzes both substrates. Both monomeric and dimeric on a 15% polyacrylamide gel containing SDS and electrophoretically cc-sarcin are effective ribonnclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…A dimeric form of α‐sarcin, a RIP with a ribonuclease activity, has been identified in a purified toxin preparation [19]. Recently, these dimers have been shown to be inactive and it has been suggested that a dimer formation could play a biological role in preventing the cytotoxicity of α‐sarcin [20]. Nevertheless, the existence of an unknown protein associated to PAP in a heterodimer cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…A dimeric form of α‐sarcin, a RIP with a ribonuclease activity, has been identified in a purified toxin preparation [19]. Recently, these dimers have been shown to be inactive and it has been suggested that a dimer formation could play a biological role in preventing the cytotoxicity of α‐sarcin [20]. Nevertheless, the existence of an unknown protein associated to PAP in a heterodimer cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…N ‐glycosidase), α‐sarcin forms a homodimer in solution that is stable during SDS‐PAGE (Sacco et al ., 1983), similar to the PAP dimer reported here. The α‐sarcin homodimer is present as a minor form, in a 1:7 ratio relative to the monomeric form, and is enzymatically inactive (Cheung et al ., 1996), characteristics shared with the PAP homodimer. Although the two proteins bear no sequence similarity to explain a common mechanism for dimerization, dimerization itself may represent a means by which cells protect their ribosomes from the toxic effects of these proteins during their synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…Ribosome-inactivating proteins, besides catalyzing ribosomes, have been known to hydrolyze many substrates [5,8,10,11,28,36]. Two major actions, the cleavage of the phosphodiester bond on the sarcin domain of rRNA in ribosomes [8,10,11] and ribonuclease activity [5,9], were the primary targets of investigation in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Two major actions, the cleavage of the phosphodiester bond on the sarcin domain of rRNA in ribosomes [8,10,11] and ribonuclease activity [5,9], were the primary targets of investigation in this study. Using combinatory genetic cloning and in vitro and in vivo analysis, the structural domains that are involved in hydrolyzing both substrates were therefore determined.…”
Section: Discussionmentioning
confidence: 99%